Customers’ impulse buying in social commerce: The role of flow experience in personalized advertising - Lia Febria Lina; Larasati Ahluwalia (Jurnal Manajemen Maranatha, 2021)
One of the advantages of using social commerce, especially Instagram, is the display of paid advertisement that are in accordance with consumer preferences or also called personalization. Previous study on the effectiveness of personalized advertising still shows mix result both positive and negative. Based on the limitations of previous research, the focus of this research is to examine and analyze the influence of personalized advertising on the value of advertising which then affects impulse purchases in social commerce and flow experience as moderation. This study using survey method on 157 active Instagram user. The findings in this result show that personalized advertising have positif affect to advertising value and encourage impulse buying. Then flow experience found strengthen effect advertising value on impulse buying. The result indicates when user has fully involved, happy, and excitement when using social media, then receive personalize advertising that match with their preference will encourage impulse buying.